Numerical Simulation for Heat Transfer of Fluid-Granular Multiphase Flow in a Preheating Furnace - Ku, Kum-Song; Myong-Il Kim; Kwang-Chol Jong; Bok-Chol Song (Sustainable Chemical Engineering, 2025)
In this paper, numerical simulations are carried out for the heat transfer of granular multiphase flow in a preheating furnace. In the preheating furnace hot air passes through a granular medium with a large particle size (> 1 cm) moving in a packed bed state. Here, a granular medium with a large particle size was considered as one with unilateral incompressibility. This method differs from the Eulerian method based on kinetic theory for granular flow. Also, the calculation of the thermal conductivity in packed bed of granular material used in the discrete element method was modified to fit the continuum model. To verify the validity of the combination of this heat conduction model and the Eulerian granular flow model based on the unilateral incompressibility, the comparison with the previous results using the discrete element method was done. The comparison showed a good agreement of the temperature distribution with time. Finally, this was applied to analyzing heat transfer in a preheating furnace and the results were compared with the measured temperatures of the discharged granular material in different conditions. The results show that the method based on the assumption of unilateral incompressibility is more suitable than the kinetic theory-based model for the analysis of heat transfer processes in granular flows with large particle sizes and dense particles that are not well entrained in fluid flow. The calculations show that the inlet charging rate should be less than 0.55 kg/s and the blast velocity higher than 100 m/s to achieve the discharged material temperature above 1,000 ℃. Also it was found that there exists a thin transition layer with a sharp temperature change at the free surface of the granular layer in the range of blast velocities (50 m/s ~125 m/s) and granular material charging rates (0.28 kg/s~1.11 kg/s) considered here.